KEEFEKTIFAN PROGRAM KLINIK BACA BERBANTUAN CERITA BERGAMBAR DALAM KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS III SEKOLAH DASAR - Dama Yanti, Alta; Suryani, Irma; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of the Reading Clinic Program assisted by illustrated stories in improving the reading comprehension skills of third-grade elementary school students. The study employed a quantitative approach with a pre-experimental research design, specifically the One-Group Pretest–Posttest design. The research sample consisted of all students of class IIIA at SDN 087/IV Kota Jambi, totaling 20 students. The data collection technique used a multiple-choice reading comprehension test that had undergone validity and reliability testing. The data were analyzed using the Shapiro–Wilk normality test, paired sample t-test, and N-Gain test with the assistance of SPSS version 20 software. The results showed that the pretest and posttest data were normally distributed, with a pretest significance value of 0.839 and a posttest significance value of 0.384 (p > 0.05). The paired sample t-test results indicated a significance value of 0.000 (p < 0.05), meaning that there was a significant difference in students’ reading comprehension skills before and after participating in the Reading Clinic Program assisted by illustrated stories. The N-Gain test result obtained an average score of 0.64, which falls into the moderate category, indicating an improvement in students’ reading comprehension skills after the treatment was given. Based on these findings, it can be concluded that the Reading Clinic Program assisted by illustrated stories is sufficiently effective in improving the reading comprehension skills of third-grade elementary school students. This program can serve as an alternative instructional strategy to help enhance students’ reading comprehension skills in elementary schools.